Exploring the Views of Individuals With Chronic Obstructive Pulmonary Disease on the Use of Rollators: A QUALITATIVE STUDY. Issue 1 (January 2018) - Holz, Alanna; Bennett, Amanda; Freethy, Amber; Rossi, Nadia; Tanzos, Megan; Goldstein, Roger; Brooks, Dina; Harrison, Samantha L.
Abstract : Purpose: Although it has been well documented that the progressive exercise limitation associated with chronic obstructive pulmonary disease can be helped with an assistive device, such as a rollator, many individuals use it infrequently. This study seeks to explore the views of individuals with chronic obstructive pulmonary disease regarding the use of rollators. Methods: A qualitative study design was used. Twelve individuals with moderate to very severe chronic obstructive pulmonary disease were recruited from an outpatient pulmonary rehabilitation program to participate in semistructured interviews. Inductive thematic analysis was applied. Results: Analysis revealed 5 themes: (1) "acquiring a rollator" reflecting the process of obtaining a device either via a health care professional or self-referral; (2) "acceptance versus resistance" describing opposing views regarding rollator usage; (3) "rollator roadblocks" describing practical barriers to use; (4) "participation" reflecting how rollators can promote reintegration into society; and (5) "revising perceptions" whereby participants embodied an eventual acceptance of rollators. Conclusion: Rollator acquisition appeared to be a unilateral, prescriptive process. Individuals described initial resistance to use, although in the long-term, negative perceptions were outweighed by the functional and social benefits of rollator use. Encouraging users to participate in deciding whether to use a rollator and providing adequate education on its indications, benefits, barriers, and facilitators are likely to promote optimal use of a rollator. Abstract : Supplemental Digital Content is Available in the Text.Rollator acquisition was often a unilateral, prescriptive process from health care professionals, with a lack of proper education regarding use and benefits, and led to suboptimal rollator use. Collaborating with patients and educating them about choosing a rollator, including problem solving through potential barriers, will promote optimal rollator use in this population.